Enhancing brain tumor detection in MRI with a rotation invariant Vision Transformer - Krishnan, Palani Thanaraj; Krishnadoss, Pradeep; Khandelwal, Mukund; Gupta, Devansh; Nihaal, Anupoju; Kumar, T. Sunil (Frontiers in Neuroinformatics, 2024)
Background The Rotation Invariant Vision Transformer (RViT) is a novel deep learning model tailored for brain tumor classification using MRI scans. Methods RViT incorporates rotated patch embeddings to enhance the accuracy of brain tumor identification. Results Evaluation on the Brain Tumor MRI Dataset from Kaggle demonstrates RViT's superior performance with sensitivity (1.0), specificity (0.975), F1-score (0.984), Matthew's Correlation Coefficient (MCC) (0.972), and an overall accuracy of 0.986. Conclusion RViT outperforms the standard Vision Transformer model and several existing techniques, highlighting its efficacy in medical imaging. The study confirms that integrating rotational patch embeddings improves the model's capability to handle diverse orientations, a common challenge in tumor imaging. The specialized architecture and rotational invariance approach of RViT have the potential to enhance current methodologies for brain tumor detection and extend to other complex imaging tasks.